2019
DOI: 10.1002/slct.201902441
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Pre and Post Ugi Modification for the Synthesis of Natural Product Inspired Fused Peptide‐Carboline Scaffolds as Potential Anti‐Leishmanial Agents

Abstract: A series of novel β‐carboline‐peptide (5 a‐5 f)/ tetrahydro‐β‐carbolines‐peptide (10 a‐10 f) has been synthesized via natural product inspired molecular hybridization approach. All the hybrids were examined for their anti‐leishmanial potential. Most of the screened derivatives exhibited significant in vitro anti‐leishmanial activity against promastigote and intracellular amastigotes (IC50 ranging from 2.43 to 7.61 μM) than the control, miltefosine (IC50 = 8.2 μM), with less cytotoxicity in comparison to the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Among the tested compounds, compounds 148, 149, and 1 50 revealed significant in-vitro anti-leishmanial activity against both promastigotes and intracellular amastigotes of L. donovani (IC 50 2.43, 3.56, and 7.61 μM, respectively) than the control drug miltefosine (IC 50 = 8.2 μM)with less cytotoxicity when compared with the standard drugs (sodium stibogluconate and Miltefosine). In-silico molecular docking studies of the synthesized compounds using the homology modeled LdTR indicated that the compound 149 showed significant binding free energy when compared with compound 1 50 ( Khan et al., 2019 ) (see Figure 18 ) .
Figure 18 Structure of compounds 148, 149 and 150 .
…”
Section: Biological Activitymentioning
confidence: 99%
“…Among the tested compounds, compounds 148, 149, and 1 50 revealed significant in-vitro anti-leishmanial activity against both promastigotes and intracellular amastigotes of L. donovani (IC 50 2.43, 3.56, and 7.61 μM, respectively) than the control drug miltefosine (IC 50 = 8.2 μM)with less cytotoxicity when compared with the standard drugs (sodium stibogluconate and Miltefosine). In-silico molecular docking studies of the synthesized compounds using the homology modeled LdTR indicated that the compound 149 showed significant binding free energy when compared with compound 1 50 ( Khan et al., 2019 ) (see Figure 18 ) .
Figure 18 Structure of compounds 148, 149 and 150 .
…”
Section: Biological Activitymentioning
confidence: 99%
“…Furthermore, coupled with other synthetic strategies, the Ugi-type reactions have also been employed for the preparation of natural product hybrids by diversification; these include terpenes, steroids, 36 alkaloids, and other metabolites, 37 and the synthesis of natural product-like compounds, particularly nitrogen heterocycles. 38 Finally, peptidomimetics integrating heterocyclic, lipidic, and sugar moieties have also been easily assembled.…”
Section: Introductionmentioning
confidence: 99%